Macro and microscopic evaluation of Gmelina arborea Roxb. – A botanical pharmacognostic approach for quality control of raw drug material - Vignesh, R M; Sumitha, V R (Plant Science Today, 2022)
Gmelina arborea Roxb. of family Verbenaceae, is one of the highly valued medicinal plant used in numerous traditional medical formulations. It belongs to the ‘Dasamoola’ group of ayurvedic medicinal plants and hence widely exploited. Pharmacognostic techniques involving macroscopic, microscopic and also dry powder analysis serve as botanical methods which help in the correct identification of the crude drug. Leaf constants such as stomatal number, stomatal index, vein islet number, vein termination number also have been determined. Better quality control practices in nutraceutical and pharmaceutical industries demand the correct identification of the dried plants or powdered drug thereby detects and prevents the adulterations, if any. The challenge ahead of this investigation is to validate the therapeutic efficacy and safety of the plant following standard methodology.